Polish Regionalism — Present Challenges and Threats - Wojciech Orłowski (Barometr Regionalny, 2013)
After the accession of Poland to the European Union our country started to be defined as a decentralized state with a regional structure. The aim of this paper is to compare Polish legal solutions to the Italian and Spanish solutions regarded as classic models of regionalism. The effect of the analysis is the conclusion that the biggest obstacle for the development of regionalism in Poland is the lack of proper legal regulations including constitutional regulations. It is responsible for the fact that Polish voivodships do not have guarantees of territorial integrity. Theoretically there is even a possibility to replace them with other units of territorial division. Other restrictions for regional development are: insufficient level of financing and the lack of formed social ties in newly formed voivodships. Due to these factors voivodships do not play their own political role. The situation could be changed as a result of an enlargement of regional competences and granting voivodships limited autonomy similarly to the situation in Italy and Spain.